Appraisal of chemical composition and biological activities of thyme essential oil: an insight to insilico molecular docking studies - Sara; Anwar, Farooq; Qadir, Rahman; Rehman, Muhammad Fayyaz ur; Mahrye; Perveen, Kahkashan; Bukhari, Najat A. (Har Krishan Bhalla and Sons, 2024)
The current study aims to ascertain the chemical composition and biological activities of thyme leaves essential oil (TEO), with an emphasis on its in silico molecular docking studies targeting the antibacterial properties of its constituents. TEO was extracted from dried leaves using a standardized procedure, with a yield of 0.75%. The chemical constituents of TEO were identified using Gas Chromatography-Mass Spectrometry (GC-MS). The primary compounds detected included carvacrol, o-acetyl thymol, α-pinene, and spathulenol. Subsequently, the antioxidant activity of the isolated oil was measured, and the results showed that the total phenolic contents (TPC) was 4.69 ± 0.17 GAE mg/100 g, the total flavonoid contents (TFC) was 1.45 ± 0.04 CE mg/100 g, the ferric reducing antioxidant potential (FRAP) ranged from 0.07-0.81, and the DPPH radical scavenging activity was 42.88-86.94%. TEO exhibited notable antibacterial activity against certain strains of Staphylococcus aureus and Escherichia coli. The molecular docking studies were then conducted to further investigate the interaction of TEO’s potent metabolites with key bacterial enzymes, identifying spathulenol and caryophyllene as the best-interacting ligands. Hemolytic activity tests of TEO indicated negligible cytotoxic effects. These findings support that TEO holds great potential for the development of functional food and nutra-pharmaceuticals.